Complex program of physical rehabilitation after saving organs operations and radical treatment of cancer of breastfor women 40–50 years in remote period - Пешкова [Olga Peshkova] Ольга Володимирівна (Slobozhanskyi Herald of Science and Sport, 2013)
In the article cited data an author about the purpose of restoration treatment and volume of rehabilitation measures for women, carrying saving organs operations and radical treatment of cancer of breast. The complex program of physical rehabilitation is described for the afore-named contingent of patients, which included medical a gymnastics with an accent on exercises, cooperant liquidations of developing complications from the side of internalss and overhead extremity on the side of operative intervention, itself massage, elements of the shallow breathing, myorelaxation, auto-training, alkaline inhalations, electrosleep, psychotherapy and dietary recommendations.